The quality of heroic living, of high endeavour and adventure : Anglican mission, women, and education in Palestine, 1888-1948 - Okkenhaug, Inger Marie. (Studies in Christian Mission, 2002)
This work focuses on Anglican mission and women's education in Palestine in the period from 1888 till 1948. As part of the \'enlightenment movement\' the project was initiated by British women educational pioneers, who influenced women to carry out the creed of academic training for girls also in colonial areas. While the educational profile of the pre-World War One schools mainly focused on modernisation of the domestic role, during the British Mandate the highly educated Anglican women teachers had two aims for their work: To create a peaceful multi-cultural environment in a society characterised by religious and ethnic strife and secondly to introduce a modern feminine ideal to Christian, Muslim and Jewish middle-and upper class girls. This study contributes to our knowledge of the Anglican missionary project, the role of women misionaries/educators and the history of Palestine.